Solving problems in the text as main way in teaching applying arithmetic - Balčytis, Bronius (Lietuvos matematikos rinkinys, 1999)
Various real-life problems are discussing in the article. Special focus is made on the problems that could be applied in everyday life of primary school pupils. The author introduces various methods of teaching.